2022
DOI: 10.1007/s40122-022-00429-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcutaneous Electrical Acupoint Stimulation Combined with Transversus Abdominis Plane Block on Postoperative Recovery in Elderly Patients Undergoing Laparoscopic Gastric Cancer Surgery: A Randomized Controlled Trial

Abstract: Introduction: This study assessed the influence of transcutaneous electrical acupoint stimulation (TEAS) combined with transversus abdominis plane block (TAPB) on the recovery of elderly patients undergoing laparoscopic gastric cancer surgery. Methods: Ninety patients (age C 60 years) undergoing laparoscopic gastric cancer surgery were randomly divided into general anesthesia group (group G), TAPB group (group NG), and TEAS combined with TAPB group (group NTG). Patients in the NTG group received TEAS at PC6, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…We found that the TEAS group had significantly lower incidence of abdominal distension and PONV, which is consistent with findings from several previous studies [ 34 , 35 ]. One possible mechanism for this effect is that acupuncture may increase the release of β-endorphin and promote the secretion of corticosteroids in the brain.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the TEAS group had significantly lower incidence of abdominal distension and PONV, which is consistent with findings from several previous studies [ 34 , 35 ]. One possible mechanism for this effect is that acupuncture may increase the release of β-endorphin and promote the secretion of corticosteroids in the brain.…”
Section: Discussionsupporting
confidence: 93%
“…TEAS is a new derivative of traditional acupuncture or electroacupuncture (EA) that may be a viable way to improve the sleep quality after surgery because of its potential to reduce pain and injury, lower infection incidence and improve patient tolerance. Some studies have demonstrated that TEAS can improve sleep quality after video-assisted thoracoscopic surgery and enhance recovery after laparoscopic gastric cancer surgery [ 34 , 35 ]. However, the impacts of TEAS on postoperative GI cancer patients and its underlying mechanism are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Five included studies [8,9,11,13,15] documented the incidence of PONV, the result suggested that TEAS reduced the incidence of PONV (RR 0.49, 95%-CI [0.32, 0.74], P = 0.007), as our previous meta-analysis indicated [4] . Additionally, 2 included studies [9,16] recorded the incidence of cough, as well as agitation [8,9] during extubation.…”
Section: Teas Reduced the Incidence Of Adverse Events During Extubationmentioning
confidence: 76%
“…We analyzed the surgical and anesthesia time in this meta-analysis. Nine included studies [8][9][10][11][12][13][14][15]17] recorded the surgical time, and 6 studies [9,10,[12][13][14]17] recorded the anesthesia time. The result suggested TEAS had no effects on surgical (SMD 0.12, 95%-CI [-0.01, 0.26], P = 0.07) and anesthesia time (SMD 0.15, 95%-CI [-0.15, 0.45], P = 0.32).…”
Section: Teas Have No Effects On Surgical and Anesthesia Timementioning
confidence: 99%
“…To the Editor, In a single-center double-blind randomized controlled trial with a total of 90 patients undergoing elective laparoscopic gastric cancer surgery, Xing et al [1] assessed the effect of transcutaneous electrical acupoint stimulation (TEAS) combined with transversus abdominis plane block (TAPB) on the outcomes of postoperative recovery. They showed that TEAS combined with TAPB enhanced early postoperative recovery defined by the quality of recovery-15 (QoR-15) score and improved postoperative pain control and immune function.…”
mentioning
confidence: 99%